THE CHILD AS DRAMATURG: investigating dramaturgical frameworks steered by child-centric sensibilities - Batzofin, Jayne (Department of Drama, 2020)
This dissertation questions how it is possible for a child to be considered the dramaturg of a theatrical production specifically catering for early year audiences. The research begins with an investigation of secondary source materials to obtain a working definition of the concepts of child/hood and dramaturg/y in relation to how other artists and art forms have used and presented work to children. The research then incorporates the use of interviews held with professionally trained theatre practitioners involved in producing and promoting Theatre for Early Years (TEY), in order to contextualise the theatre scene for early years in South Africa at present. The majority of the research is then dedicated to analysing, through my own artistic practice, the means by which children participated in the process of developing a TEY production in 2015. Whereby dramaturgy is understood to be a political practice that addresses the inequality of power relations between the audience and the performance, the main outcome of the dissertation addresses the value of including the child as a dramaturg/quasi-dramaturg in the practice of devising theatre for young audiences.